2016
DOI: 10.3390/ijms17121982
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Non-Canonical Functions and Regulation by p53: p53 and Stemness

Abstract: Since its discovery nearly 40 years ago, p53 has ascended to the forefront of investigated genes and proteins across diverse research disciplines and is recognized most exclusively for its role in cancer as a tumor suppressor. Levine and Oren (2009) reviewed the evolution of p53 detailing the significant discoveries of each decade since its first report in 1979. In this review, we will highlight the emerging non-canonical functions and regulation of p53 in stem cells. We will focus on general themes shared amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 273 publications
(340 reference statements)
4
90
0
Order By: Relevance
“…Moreover, one would not presume a priori that the p53 output generated by DNA damage would exactly mirror the gene expression signature elicited by oncogene activation, even in a single cell type. Despite data indicating that p53 can, in principle, control a wide variety of biological processes (reviewed in Olivos and Mayo, 2016), the physiological settings in which one or more processes predominate are incompletely understood and deserve more systematic study.…”
Section: P53 Controls a Broad And Flexible Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, one would not presume a priori that the p53 output generated by DNA damage would exactly mirror the gene expression signature elicited by oncogene activation, even in a single cell type. Despite data indicating that p53 can, in principle, control a wide variety of biological processes (reviewed in Olivos and Mayo, 2016), the physiological settings in which one or more processes predominate are incompletely understood and deserve more systematic study.…”
Section: P53 Controls a Broad And Flexible Networkmentioning
confidence: 99%
“…In stem and progenitor cells of the hematopoietic system, liver, brain, and breast, p53 restricts cellular self-renewal (Friedmann-Morvinski et al, 2012; Tosoni et al, 2015; Tschaharganeh et al, 2014). Trp53 -null mice consequently have expanded numbers of tissue specific stem cells, highlighting its importance in maintaining tissue homeostasis (Olivos and Mayo, 2016). p53 limits cellular plasticity (governing transition between cell states) and, at its extreme, the ability of somatic cells to undergo epigenetic reprogramming into induced pluripotent stem cells (Olivos and Mayo, 2016).…”
Section: The Origins Of P53mentioning
confidence: 99%
See 1 more Smart Citation
“…In response to a mutagenic or stress stimulus (e.g., nutrient deprivation) or changes in cell signalling and tissue homeostasis, p53 is activated, initiating different adaptive protein expression programs to maintain/restore tissue integrity and biological functions by triggering and coordinating different cell fate decisions in the diverse cell types composing the damaged organs. p53 induces and coordinates cell repair, cell survival, senescence, migration of immune, endothelial and progenitor cells, stem-cell renewal, differentiation and cell death depending on the cell type and function, the active signalling pathways, the type of damage, the cell cycle stage, nutrient availability, the immune response and the presence of pathogens [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that p53 suppresses the self-renewal and osteogenic differentiation properties, which may be rescued via p53 RNA interference (21). In CSCs, p53 was also determined to regulate the maintenance of stemness (22). Hegde et al (23) determined that, in leukemia stem cells (LSC), overexpression of wild-type p53, but not mutant p53 lacking DNA binding activity, resulted in LSCs gaining properties, such as proliferating and invasive capacities, and losing their self-renewal capacity.…”
Section: Introductionmentioning
confidence: 99%